Environment Friendly Management Strategy for Root-Knot Nematode, Meloidogyne incognita on Cluster Bean (Cyamopsis tetragonoloba L.) under Field Condition (Indian Journal of Nematology, 2024)
Cluster bean is a cash crop growing in all parts of Rajasthan and root-not nematode, Meloidogyne incognita is one of constraint and hidden foe of this crop. It does much loss to crop than other pests. A management trial was conducted in two Kharif seasons on farmer’s field naturally infested with root-knot nematode, M. incognita to find out the efficacy of bio-agents viz., Paecilomyces lilacinus, Pochonia chlamydosporia, and Pseudomonas fluorescens at 0.5, 1 and 2 per cent w/w as seed treatment against rootknotnematode, M. incognita infecting cluster bean. Results exhibited that T. harzianum at 2 per cent w/w was most effective followedby P. lilacinus at 2 per cent w/w and P. chlamydosporia at 2 per cent w/w in terms of reducing the infection of root-knot nematode, M.incognita and increasing the yield of cluster bean.